Strategi kesopanan dalam persuasi oleh juri The Voice Indonesia dan Amerika Serikat: Studi pragmatik lintas budaya - Harris, Syahzanan; Sartini, Ni Wayan (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2025)
This study aimed to examine the politeness strategies used by The Voice Indonesia and USA judges in persuading participants and discovered how cultural differences affect the differences in persuasion. This study uses the politeness strategies theory by Brown and Levinson (1987) to see the strategy of using persuasive politeness strategies, the CCSARP theory by Blum-Kulka et al. (1989) to discover differences in communication culture, and the high-context culture and low-context culture theory by Hall (1976) to show the differences in culture between Indonesia and the USA. The study results indicate that The Voice Indonesia judges predominantly use negative politeness and off-record, which indicates a tendency towards an indirect communication culture. In contrast, The Voice USA judges often use bald on-record and positive politeness, which tends to be a direct communication culture. It shows an influence of high-context culture based on collectivism in Indonesia to prioritize harmony and mutual harmony, while low-context culture in the USA based on individualism tends to prioritize personal interests.